2002
DOI: 10.2105/ajph.92.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Stigma and Shame to Gonorrhea and HIV Screening

Abstract: Shame is part of the experience of seeking STD-related care, but stigma may be a more powerful barrier to obtaining such care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
295
1
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 380 publications
(320 citation statements)
references
References 11 publications
17
295
1
5
Order By: Relevance
“…Not wanting to be labelled as a drug-user which implies accepting a stigmatised identity was a barrier to engaging with treatment services. This finding echoes other sensitive research on gonorrhoea and HIV screening where stigma posed a barrier to help-seeking (Fortenberry et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Not wanting to be labelled as a drug-user which implies accepting a stigmatised identity was a barrier to engaging with treatment services. This finding echoes other sensitive research on gonorrhoea and HIV screening where stigma posed a barrier to help-seeking (Fortenberry et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…These barriers include fear; stigma; shame; denial; lack of social support; lack of confidential services; lack of health insurance options especially as they get older; and not knowing where to go for care. [141][142][143][144][145][146] Given the asymptomatic nature of many STIs, including HIV infection, strategies are needed to raise young men's awareness about sexual/reproductive health services, STI and HIV testing options, and related resources. Promoting sexual/reproductive health for young men can lead to sexual responsibility, healthy intimate relationships, and responsible fatherhood.…”
Section: Male Adolescents' Sexual/ Reproductive Health Care Usementioning
confidence: 99%
“…We hypothesized that our measure of internalized stigma would be strongly and positively correlated (r=0.5-0.7) with feelings of shame. Shame is one psychological experience an individual may have as a result of internalized stigma, and several studies in the literature have demonstrated these constructs to be separate, but related (Cunningham et al, 2002;Duffy, 2005;Fortenberry et al, 2002). Studies of HIV-positive adults living in the US have also demonstrated that stigma is associated with poor social support and depressive symptoms (Bairan et al, 2007;Carr and Gramling, 2004;Sowell et al, 1997;Vanable et al, 2006).…”
Section: Content and Construct Validity Of Stigma Measurementioning
confidence: 99%